2022
DOI: 10.3389/fpubh.2022.1007769
|View full text |Cite
|
Sign up to set email alerts
|

High morbidity and mortality associated with primary bloodstream infections among pediatric patients with cancer at a Guatemalan tertiary referral hospital

Abstract: Infectious complications remain major contributors to adverse outcomes in patients treated for non-communicable disease, particularly in resource limited settings. We performed a 5-year retrospective study of primary bloodstream infections at a dedicated pediatric oncology center in Guatemala. Two hundred and twelve episodes occurring in 194 unique patients qualified for inclusion. Patients required intensive care unit admission in 55% of episodes and death occurred in 24% of episodes. Despite subspecialty sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Recently, nearly half of blood infections worldwide occurred in children; notably, almost 2.9 million children younger than five years have died from sepsis [ 2 , 3 , 4 ]. Globally, gram-negative bacteria accounted for a majority of pathogens in children with BSIs, followed by gram-positive bacteria and fungi [ 5 , 6 , 7 ]. Generally, the most common gram-negative bacterial isolates were Klebsiella spp., Escherichia coli ( E. coli ), Acinetobacter baumannii ( A. baumannii ), and Pseudomonas aeruginosa ( P. aeruginosa ), and the most frequent gram-positive bacterial isolates were Staphylococcus aureus ( S. aureus ), Group B Streptococcus (GBS), Coagulase-negative Staphylococci (CoNS), and Enterococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nearly half of blood infections worldwide occurred in children; notably, almost 2.9 million children younger than five years have died from sepsis [ 2 , 3 , 4 ]. Globally, gram-negative bacteria accounted for a majority of pathogens in children with BSIs, followed by gram-positive bacteria and fungi [ 5 , 6 , 7 ]. Generally, the most common gram-negative bacterial isolates were Klebsiella spp., Escherichia coli ( E. coli ), Acinetobacter baumannii ( A. baumannii ), and Pseudomonas aeruginosa ( P. aeruginosa ), and the most frequent gram-positive bacterial isolates were Staphylococcus aureus ( S. aureus ), Group B Streptococcus (GBS), Coagulase-negative Staphylococci (CoNS), and Enterococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Regional and country-specific descriptions highlight drastic variability of prevalence of BSI episodes (14.1–29.4%), predominant bacterial isolates, antibiotic-resistant patterns and approaches to treatment in paediatric patients with cancer 10–15. Patients with cancer do not receive timely antibiotic administration and infectious diagnostic evaluations, which may contribute to high mortality 11–13 16. Tertiary institutions in SSA countries, Kenya included, have documented variable clinical approaches to paediatric patients with cancer with fever; 14.1–16% of patients with fever get blood cultures, and only 23% have antibiotics given within 3 hours of fever onset 9 12.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high disparity of infection-related mortality of fever episodes in children with cancer in SSA,9 12 13 urgent attention should be given to improve the timely diagnosis and management of fever episodes in children with cancer 9 16. Treatment guidelines have largely relied on evidence from high-income countries,3 unpublished data from treatment centres and anecdotal experience.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms may appear according to the age of the child, the location of the infection, and the pathogens causing it [2]. Some studies have reported that the initial levels of mortality rates up to 42% [3] Children with leukemia often have prolonged neutropenia, suppression in the immune system, skin damage, and alteration in nature of the gastrointestinal mucosa as a result of blood cancer, administration of chemotherapy, radiotherapy, and prolonged hospitalization. All these factors make these patients vulnerable to highrisk bloodstream infections by multiple microbiological agents [4,5].…”
Section: Introductionmentioning
confidence: 99%